Entre o negro e o branco: tons e sentidos- a(s) formação(ões) discursiva(s) dos/nos poemas de Ifá - Carvalho, Juliano Araújo (2013)
This dissertation, entitled \"Between the black and the white: tones and senses the discursive formation(s) in the poems of Ifá\", aims at studying the discursive formations present and constituent in mythical texts originating from of a consultation to the oracle of Ifá, characterizing this work as a case study. The theoretical foundation of this research is Michel Pêcheux s Discourse Analysis and the theoretical extension of Santos (2009), whohas coined the notion of Enunciative Instance of Subjectivity. Based on a hermeneutic, heuristic and holistic paradigm, this work has the following objectives: i) to identify the discursive formations in the discourse of Ifá; ii) to interpret the movements of the Enunciative Instance of Subjectivity, according to Santos (2009), in the discursive registrations and in the movements of identification and desidentification with the discursive formations; and, iii) to identify possible indices of (ir)regularity that can denote the characterization of a discursive formation of Ifá. There fore, the object of this work - whose thirteen excerpts constitute the analyzed corpus- is the linguistic materiality emerged during a consultation to the oracle of Ifá and an interview realized with the babalawo, a priest responsible for the consultation. Thus, the analyze was accomplished starting from mapping matrixes, that has allowed to observe the conditions of production of the discourse, the conjunctures of senses and the movements of the Enunciative Instance of Subjectivity. So, a necessary illusion of entirety was established and this illusion has created an opportunity to conclude this work, in his singularity, with reflections about the discursive formation(s) in the poems of Ifá.